2014
DOI: 10.1021/ic501923s
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Silicide Nanocrystals: Synthesis, Chemical Stability, Thermal Stability, and Carbon Encapsulation

Abstract: Lithium silicide (LixSi) is the lithiated form of silicon, one of the most promising anode materials for the next generation of lithium-ion batteries (LIBs). In contrast to silicon, LixSi has not been well studied. Herein we report a facile high-energy ball-milling-based synthesis of four phase-pure LixSi (x = 4.4, 3.75, 3.25, and 2.33), using hexane as the lubricant. Surprisingly, the obtained Li3.75Si phase shows significant downward shifts in all X-ray diffraction peak positions, compared with the standard.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 78 publications
(215 reference statements)
0
39
0
Order By: Relevance
“…It has been reported that Li 21 Si 5 is the most thermally stable phase among the crystalline lithium silicates [21]. The XRD patterns of the four Li x Si/Li 2 O composites are similar, indicating that pristine particle size does not have a big effect on the formation of crystalline Li 21 Si 5 . As calculated by the Scherrer equation, the crystalline sizes of the four composites are 28.2, 29.3, 31.9 and 37.5 nm, indicating that the SiO 2 microparticles produce relatively large Li 21 Si 5 domains.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…It has been reported that Li 21 Si 5 is the most thermally stable phase among the crystalline lithium silicates [21]. The XRD patterns of the four Li x Si/Li 2 O composites are similar, indicating that pristine particle size does not have a big effect on the formation of crystalline Li 21 Si 5 . As calculated by the Scherrer equation, the crystalline sizes of the four composites are 28.2, 29.3, 31.9 and 37.5 nm, indicating that the SiO 2 microparticles produce relatively large Li 21 Si 5 domains.…”
Section: Resultsmentioning
confidence: 76%
“…A home-made sealed sample holder was used to avoid exposing the products to the air. The diffraction peaks of Li 2 O and Li 21 Si 5 are shown in the Figure 3a, demonstrating the formation of Li 2 O (PDF# 04-001-893) and Li 21 Si 5 (PDF# 00-018-747) phases. It has been reported that Li 21 Si 5 is the most thermally stable phase among the crystalline lithium silicates [21].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This "lithiophobic" effect possibly originates from the lack of bonding interaction between surface (carbon or Cu) and molten Li (27,28). For surface-modified objects, the Si coating reacts with molten Li to create a binary alloy phase-lithium silicide with some bonding interactions to pure Li (29)(30)(31). This reaction drives and guides molten Li to wet the entire surface and fill in the porous structure (28).…”
Section: Resultsmentioning
confidence: 99%